Planning the Development of Competencies to Enhance the Professionalism of Educators in Islamic Religious Educational Institutions - Farid, Miftah; Nugraha, Mulyawan Safwandy (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
Non-formal education can play a role as a complement, addition, and substitute for formal education. One form of non-formal education in Islamic religious education is the establishment of the Taman Pendidikan Al-Qur’an (TPQ). The management of ustadz and ustadzah as human resources at the Taman Pendidikan Al-Qur’an (TPQ) is crucial, particularly concerning competency development planning to enhance their professionalism. This research was conducted at TPQ Darul Muzakkirin, utilizing qualitative research methods with data collection techniques including interviews, observations, and documentation. The collected data were analyzed using the Miles & Huberman analysis model, involving data collection, data reduction, data presentation, and drawing conclusions. The research findings conclude that competency development planning is not optimal as the acquired material does not align with the needs and lacks relevance for ustadz and ustadzah. Therefore, the recommendation that can be made through this paper is to use the TPACK (Technological Pedagogical Content Knowledge) model as a framework for planning the development of educator competencies at TPQ Darul Muzakkirin.